Effective spin-orbit models using correlated first-principles wave functions - Yueqing Chang; Lucas K. Wagner (Physical Review Research, 2020)
Diffusion Monte Carlo using continuous real-space wave functions is one of the most accurate scalable many-body methods for solid-state systems. However, to date, spin-orbit interactions have not been incorporated into large-scale calculations at a first-principles level, only having been applied to small systems. In this technique, we use explicitly correlated first-principles diffusion Monte Carlo calculations to derive an effective spin-orbit model Hamiltonian. The simplified model Hamiltonian is then solved to obtain the energetics of the system. To demonstrate this method, benchmark studies are performed in main-group atoms and monolayer tungsten disulfide, where high accuracy is obtained.